2017
DOI: 10.21815/jde.017.079
|View full text |Cite
|
Sign up to set email alerts
|

Postdoctoral Teaching of Geriatric Dentistry in U.S. Dental Schools

Abstract: The aim of this study was to determine the number and size of postdoctoral teaching programs in geriatric dentistry in U.S. dental schools and other health professions educational institutions and those programs with Health Resources and Services Administration (HRSA) funding. In 2015, all 67 U.S. dental schools were contacted via email with a questionnaire to ask if they had a postdoctoral program in geriatric dentistry; if they did, they were asked to report the length and size of the program. Directors of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…At the dental professional level, although 92.8% of U.S. dental schools teach geriatric dentistry as a compulsory course, and 84.9% of those teach the topic “Restorative management of persons with Alzheimer's disease and other dementias,” only 57.1% had some compulsory clinical education in geriatric dentistry and it is unsure how much of this clinical training involves patients with dementia. A small number of dentists have received advanced training in geriatric dentistry in the United States, and there is a shortage of current fellowship programs …”
Section: Oral Health Status Among Patients With Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…At the dental professional level, although 92.8% of U.S. dental schools teach geriatric dentistry as a compulsory course, and 84.9% of those teach the topic “Restorative management of persons with Alzheimer's disease and other dementias,” only 57.1% had some compulsory clinical education in geriatric dentistry and it is unsure how much of this clinical training involves patients with dementia. A small number of dentists have received advanced training in geriatric dentistry in the United States, and there is a shortage of current fellowship programs …”
Section: Oral Health Status Among Patients With Alzheimer's Diseasementioning
confidence: 99%
“…A small number of dentists have received advanced training in geriatric dentistry in the United States, and there is a shortage of current fellowship programs. 61 At the patient level, aggressiveness of the patients has been consistently reported as a barrier for providing appropriate oral hygiene care, and many techniques have been reported to overcome this barrier. 7 Patient inability to communicate oral pain or discomfort has also been reported as a barrier to providing adequate oral health care.…”
Section: Access To Oral Health Care: Barriers and Enablersmentioning
confidence: 99%
“…Also, there were 41 dental schools which had an Advanced Education in General Dentistry (AEGD) or GPR programs. In a recently published update, Ettinger et al . found that of the 18 training sites funded by HRSA had their financial support removed in 2015.…”
Section: Advanced Training In Geriatric Dentistrymentioning
confidence: 99%
“…16,18 Nevertheless, it is critical to prepare the oral health care workforce to help promote the wellbeing of older adults through maintaining good oral health. 19,20 At the University of Iowa College of Dentistry and Dental Clinics, the Geriatrics and Special Need Dentistry Program has developed a teaching tool designed to help students learn and apply the thought process of the expert about how to integrate the previously taught theoretical knowledge regarding the multiple modifying factors affecting older adults and then assess the risk of ROHD and implement customized treatment plans, in a systematic manner.…”
Section: Introductionmentioning
confidence: 99%